Noble Character Development Through Child-Friendly School Programs - Moh. Faiz Maulana; Aris Adi Leksono (IAIN Syekh Nurjati Cirebon, 2023)
The rise of cases of violence against children in schools is a strong reason for the need for the protection of children's rights. In this regard, an educational revolution is needed as an effort to reform the education system to be able to create a learning environment that is able to respect and fulfill children's rights. SMPN 52 Jakarta is one of the schools that implement the Child-Friendly School program to realize children's rights to quality education. This study aims to describe the programs, strategies, and impacts of implementing Child-Friendly Schools at SMPN 52 Jakarta. This study uses a qualitative research approach. The data in this study were collected using interview techniques using interview sheets, observation techniques using field notes, and documentation using checklist sheets. Data in this study were collected and analyzed through the following procedures or stages: compiling research instruments, arranging permits, conducting field surveys, selecting and determining informants, conducting simultaneous data collection, checking related to data completeness, classifying data, and analyzing data. This research succeeded in getting an overview of the development of noble character through a child-friendly school program. The Child-Friendly School Program at SMPN 52 Jakarta has also been implemented by integrating all existing school policies, school programs, and school activities.